Optimization of Ion-Ligand Stoichiometry in Synthesis of Ionic Imprinted Polymer for Selective Fe(III) Adsorption - Auliya, Tazkiya; Basukiwardojo, Maria Monica Sianita (Journal of The Indonesian Society of Integrated Chemistry, 2025)
This study investigates the influence of the complex structure formed between the template ion and the ligand on the adsorption efficiency of metal ions by Ionic Imprinted Polymer (IIP). The IIP was synthesized with ion-template/ligand stoichiometric ratios of 1:1, 1:2, 1:3, 1:4, and 1:5 via precipitation polymerization. Materials used in synthesis are Fe(NO₃)₃ as the template ion, EDTA as the ligand, MAA as the functional monomer, EGDMA as the cross-linker, and BPO as the initiator. Adsorption experiments confirmed that the IIP prepared with a 1:1 Fe(III)/EDTA ratio exhibited the highest maximum adsorption capacity of 5.18 mg/g, outperforming other stoichiometric compositions. Characterization of the IIP(1:1) using FTIR confirmed the presence of functional groups corresponding to Fe-EDTA interactions in the Non-Imprinted Polymer (NIP), while such interactions were absent in the IIP, indicating successful template removal and the formation of binding cavities suitable for selective metal ion adsorption.  EDX analysis also revealed a difference in Fe(III) content, with the NIP at 0.52% and the IIP at 0.36%. Results reveal that the IIP exhibits selective adsorption toward the target ion, indicating its potential for selective metal ion separation and environmental remediation